2007
DOI: 10.1016/j.biomaterials.2007.08.005
|View full text |Cite
|
Sign up to set email alerts
|

Stress–corrosion crack growth of Si–Na–K–Mg–Ca–P–O bioactive glasses in simulated human physiological environment

Abstract: This paper describes research on the stress-corrosion crack growth (SCCG) behavior of a new series of bioactive glasses designed to fabricate coatings on Ti and Co-Cr-based implant alloys. These glasses should provide improved implant fixation between implant and exhibit good mechanical stability in vivo. It is then important to develop an understanding of the mechanisms that control environmentally-assisted crack growth in this new family of glasses and its effect on their reliability. Several compositions ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 55 publications
0
14
0
Order By: Relevance
“…However, in PBS at 37 °C, the mean fatigue life showed a significant decrease from 10 5.9 cycles to 10 4.2 cycles for the same increase in the stress amplitude. The observed trend for the effect of stress and aqueous environment on the fatigue of silicate 13–93 bioactive glass scaffolds is compatible with the stress corrosion crack growth mechanisms for bioactive and conventional silicate glasses [44] which is generally attributed to the stress corrosion of Si–O–Si bonds at the crack tip [45]. In normal walking, the compressive load on the human femur is estimated to be smaller than 4 times the body weight [46].…”
Section: Discussionmentioning
confidence: 53%
“…However, in PBS at 37 °C, the mean fatigue life showed a significant decrease from 10 5.9 cycles to 10 4.2 cycles for the same increase in the stress amplitude. The observed trend for the effect of stress and aqueous environment on the fatigue of silicate 13–93 bioactive glass scaffolds is compatible with the stress corrosion crack growth mechanisms for bioactive and conventional silicate glasses [44] which is generally attributed to the stress corrosion of Si–O–Si bonds at the crack tip [45]. In normal walking, the compressive load on the human femur is estimated to be smaller than 4 times the body weight [46].…”
Section: Discussionmentioning
confidence: 53%
“…In recent works, the possibility of fabricating glass or ceramic coatings on metallic alloys using different techniques2, 3 such as plasma spraying4, sol‐gel,5, 6 biomimetic process,7 magnetron sputtering,8 radiofrequency sputtering,8 electrophoretic deposition,9, 10 or a simple enameling technique11–17 among others such as dip coating, physical vapor deposition, ion‐beam, for instance, has been demonstrated. These graded glass layers can be modified by introducing calcium phosphate (CP) mixtures to control the dissolution rates.…”
Section: Introductionmentioning
confidence: 99%
“…A linear relation is observed between the crack-growth speed and the indentation load, which is in good accordance with Eq. (6). The result suggests the presence of the stress-assisted crack propagation in the 45S5 bioglass, when the indented 45S5 bioglass was immersed in the PBS solution.…”
Section: Materials Dissolutionmentioning
confidence: 83%
“…Reis et al [5] observed the degradation of the hydroxyapatite coatings on Ti-6Al-4V substrate through surface cracking and faster dissolution when subjected to cyclic bending. Bloyer et al [6] evaluated the stress-corrosion crack growth of Si-based bioactive glasses in the SBF solution. Li et al [1] recently studied the stress effect on the material dissolution of 45S5 bioglass in the PBS solution using the Vickers indentation.…”
Section: Introductionmentioning
confidence: 99%